2017
DOI: 10.1038/s41598-017-13145-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phosphorylation and assembly of photosystem complexes and redox homeostasis in two wheat cultivars with different drought resistance

Abstract: Reversible phosphorylation of proteins and the assembly of thylakoid complexes are the important protective mechanism against environmental stresses in plants. This research was aimed to investigate the different responses of the antioxidant defense system and photosystem II (PSII) to osmotic stress between drought-resistant and drought-susceptible wheat cultivars. Results showed that the decrease in PSII photochemistry and six enzyme activities was observed in drought-susceptible wheat compared with drought-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 79 publications
3
40
1
4
Order By: Relevance
“…Photosynthetic pigments are among the most important indicators of responses to environmental stresses [9,33,37,38]. In the present study, although Chl a/b showed no obvious changes under high light, total Chl contents significantly declined under high light.…”
Section: Discussioncontrasting
confidence: 44%
“…Photosynthetic pigments are among the most important indicators of responses to environmental stresses [9,33,37,38]. In the present study, although Chl a/b showed no obvious changes under high light, total Chl contents significantly declined under high light.…”
Section: Discussioncontrasting
confidence: 44%
“…The chlorophyll a to chlorophyll b ratio (Chl a/b) is one of basic plant characteristics and provides information about the overall condition of plants and possible stress effects. Chl a/b tends to increase with increasing stress due to conversion of chlorophyll b to chlorophyll a (Chen et al, 2017; Table 1). The total content of xanthophyll cycle pigments (V + A + Z, i.e., the sum of violaxanthin, antheraxanthin and zeaxanthin) provides information on plant-protective activity, as these pigments are involved in dynamic interconversion through the operation of the xanthophyll cycle (Forster et al, 2011;Esteban et al, 2015) thus increasing in stressful conditions ( Table 1).…”
Section: Photosynthetic and Photoprotective Pigmentsmentioning
confidence: 99%
“…Plants have developed several enzymatic and non-enzymatic antioxidant protection mechanisms to counteract the damaging effects of ROS under environmental stresses (Wang et al, 2010). At the same time, plants can deal with environmental stresses through increasing dissipation of excess excitation energy or synthesizing and accumulating some stress-resistant substances (Chen et al, 2017). During the last 50 years, global climate change has significantly adverse effects on crop yields because of the increases in drought and heat stresses (Hillel and Rosenzweig, 2002).…”
Section: Introductionmentioning
confidence: 99%